Import tariff led export under-invoicing: a paradox - Amit K. Biswas (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2009)
Prolonged worldwide economic depression forces some economists and policy makers to demand for a tougher regulation to protect their domestic economy. If implemented, this may lead to a high tariff and non-tariff regime that ruled the pre-globalised world economy. This paper examines the consequences of a tariff protected trade regime. It takes up the case of trade misreporting phenomena under the framework of protected regime. It builds up a basic trade mis-invoicing model and then develops a collusion between underreporting traders of partner countries. I show that high tariff barrier gives incentives not only to the importers but also to the exporters to gain by underreporting the trade statistics. Interestingly, this paper shows that even if foreign exchange is fully floated, underground foreign exchange market can be created and exporters may rationally underreport without any gain through black market premium a departure from conventional theory.
Keywords: F13; F31; K42; 330; Prohibitive Tariff; Misreporting of Trade Data; Collusion